Komputerisasi Pengolahan Data Rekam Medis Pasien Rawat Jalan di Klinik Pratama - Nurhayati, Nurhayati; Widodo, Sri; Rahmawati, Nur Rizka (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Pratama clinics as first-level health care facilities have an important role in patient care and must be able to manage patient medical record data accurately and quickly. Dr. Anton's Primary Clinic as the object of research has problems in managing medical record data, including high patient visits, medical record data processing is still manual, so there is still a lot of data that is not sustainable and difficulties in report recapitulation. This study aims to produce a computer program that is able to process medical record data of outpatients effectively. The scope of research on the development of information systems. Research methods include data collection, system development and implementation. The research is qualitative with descriptive method. Data collection is through observation and interviews. System development applies the concept of the waterfall model. The research resulted in computer products processing outpatient medical record data. The conclusion of this research has been able to produce computerized data processing of outpatients that are able to support the services of pratama clinic patients effectively and efficiently.